Partners of Zaynab : A Gendered Perspective of Shia Muslim Faith - D'Souza, Diane, 1960- (Book collections on Project MUSE., 2013)
How do pious Shia Muslim women nurture and sustain their religious lives? How do their experiences and beliefs differ from or overlap with those of men? What do gender-based religious roles and interactions reveal about the Shia Muslim faith? In Partners of Zaynab, Diane D'Souza presents a rich ethnography of urban Shia women in India, exploring women's devotional lives through the lens of religious narrative, sacred space, ritual performance, leadership, and iconic symbols. Religious scholars have tended to devalue women's religious expressions, confining them to the periphery of a male-centered ritual world. This viewpoint often assumes that women's ritual behaviors are the unsophisticated product of limited education and experience and even a less developed female nature. By illuminating vibrant female narratives within Shia religious teachings, the fascinating history of a shrine led by women, the contemporary lives of dynamic female preachers, and women's popular prayers and rituals of petition, Partners of Zaynab demonstrates that the religious lives of women are not a flawed approximation of male-defined norms and behaviors, but a vigorous, authentic affirmation of faith within the religious mainstream. D'Souza questions the distinction between normative and popular religious behavior, arguing that such a categorization not only isolates and devalues female ritual expressions, but also weakens our understanding of religion as a whole. Partners of Zaynab offers a compelling glimpse of Muslim faith and practice and a more complete understanding of the interplay of gender within Shia Islam.